TEMPLE OF SCIENCE: МOSAIC OF M. A. STOROZHENKO IN THE INTERIORS OF THE BOGOLYUBOV INSTITUTE FOR THEORETICAL PHYSICS, NAS OF UKRAINE IN THEOPHANY - Тарасенко, О. А.; Тарасенко, А. А.; Кубриш, Н. Р. (Art and Design, 2020)
The purpose of the article is to study the history of creation and ideological content of mosaics MykolaAndrievichStorozhenko (1928–2015) in the interior of the Bogolyubov Institute for Theoretical Physics, NAS of Ukraine, Theophany (1969) in the context of Ukrainian and world heritage of monumental art. The study used historical-cultural, comparative, iconographic and iconologic methods. We rely on the theory of "big time" by M. M. Bakhtin, that allows us to consider the mosaic M. A. Storozhenko with the legacy of world art. The significance of the artistic images of the enlighteners as the apostles of spiritual and scientific knowledge – the pillars of the Temple of Science is shown. Artistic-stylistic analysis revealed the features of the embodiment of the idea of scientific and cultural interconnection of generations of Ukrainian scholars-educators by means of monumental art. The importance of the heritage of national and world art in the addition of the individual style of M. A. Storozhenko is studied. The role of ornament as a national code for the embodiment of the idea of the connection between the clan and the people is revealed. The significance of mosaics in the history of monumental art of Ukraine is determined. The philosophical, cultural and historical content of the monumental compositions of M. A. Storozhenko was studied in conjunction with the problems of national self-identification and polystylism of twentieth-century art. The results of the study are necessary to create the history of monumental decorative art of Ukraine at the modern level of art history.